Lasers - Siegman Anthony E (University Science Books, 1986)
Lasers is both a textbook and a general reference book with an emphasis on basic laser principles and theory. A unique feature is that it gives a complete, detailed, and accurate treatment of laser physics, building only on classical models, without requiring the reader to have a quantum mechanical background. It is for all scientists and engineers who work with lasers.